PENANGULANGAN KREDIT MACET PADA PEMBIAYAAN MURABAHAH DI BANK RAKYAT INDONESIA SYARIAH KCP. CIANJUR - Khoirunisa, Ulfah; Arifin, Asep (Al-Muamalat: Jurnal Ekonomi Syariah, 2018)
In a developing economy, people need financial capital to open businesses and expand their business. Business actors obtain financial capital from the bank. This is due to easier access to banking and wider networks in various regions. For that reason, the review of the Shari'ah Law Economics Law on the claims of loan financing (murabaha) of bad debts in LKS is important. Taking into account the phenomenon, the study of Islamic financial institutions, especially regarding the review of Islamic law on financing guarantees and bad credit risk management, becomes something new that deserves to be studied in depth. This study aims to determine the factors that cause the occurrence of problem financing, what things have been applied by Bank BRI Syariah in tackling the problematic financing and how the mechanism of cooperation with the askrindo, and see how the review of Islamic Law Law against the prevention of bad debts in murabahah financing. Murabahah according to the Law No.21 of 2008 concerning Sharia Banking is a Financing Agreement of an item by asserting its purchase price to the buyer and the buyer pays it at a more price as an agreed profit. The research method used is descriptive analysis method, that is research focused on a particular case to be observed and dianalasis thoroughly until thoroughly. The type of data used is the primary data that contains interview author to staff employees BRI Syariah KCP Cianjur either directly or indirectly and secondary data that support in solving research problems. The data collection techniques used through interviews to BRI Syariah and several journals on the problem of bad loans. Based on the result of the research, (1) Factors that cause problem financing in Bank BRI Syariah KCP Cianjur caused by debtor and creditor factor, coping mechanism murabahah stalled in Bank BRI Syariah KCP Cianjur in cooperation with ASKRINDO seen from cause factor congestion because that is handled by the ASKRINDO only a few factors such as fire, sea transport, and motor vehicles, (2) The review according to Al-Qura'an and Al-Hadist against the prevention of bad financing in Murabahah financing in Bank BRI Syariah KCP Cianjur not in accordance with which is contained in Al-Qur'an and Al-Hadist where doing the prevention through mediation with the creditor first and the creditor does not provide openness when making a collective agreement. However, the debtor is not aware of the presence of ASKRINDO in the prevention of bad debts in BRI Syariah KCP Cianjur.